2009
DOI: 10.4064/fm203-2-4
|View full text |Cite
|
Sign up to set email alerts
|

Set-theoretic constructions of two-point sets

Abstract: Abstract. A two-point set is a subset of the plane which meets every line in exactly two points. By working in models of set theory other than ZFC, we demonstrate two new constructions of two-point sets. Our first construction shows that in ZFC + CH there exist two-point sets which are contained within the union of a countable collection of concentric circles. Our second construction shows that in certain models of ZF, we can show the existence of two-point sets without explicitly invoking the Axiom of Choice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…However, to demonstrate the existence of n-point sets for 2 ≤ n < ℵ 0 , it seems apparent that we must resort to transfinite techniques. The standard approach, which we take in this paper, is essentially due to Mazurkiewicz 2 [13] and is based on the existence of a wellordering of the real line, but we note that Chad et al [3] describe an alternative construction of two-point sets which is consistent with ZF and requires only that some suitable fragment of the real line be well-ordered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to demonstrate the existence of n-point sets for 2 ≤ n < ℵ 0 , it seems apparent that we must resort to transfinite techniques. The standard approach, which we take in this paper, is essentially due to Mazurkiewicz 2 [13] and is based on the existence of a wellordering of the real line, but we note that Chad et al [3] describe an alternative construction of two-point sets which is consistent with ZF and requires only that some suitable fragment of the real line be well-ordered.…”
Section: Introductionmentioning
confidence: 99%
“…Mauldin gave three problems concerning two-point sets, and to this day, the only remaining problem is to determine if a two-point set can be chosen to be a Borel subset of the plane. 3 This problem is apparently very deep, and it is likely that if we are to make any progress on it, then we will need to further our knowledge about the structure of two-point sets.…”
Section: Introductionmentioning
confidence: 99%
“…Lemma 1 is Lemma 4.1 of [1]. As stated in [1], it says that there are at most 23 possible r; this does not seem to be the optimal number.…”
mentioning
confidence: 99%
“…There have been other constructions of 2-point sets such as in [3] where it was shown that they exist in arbitrary vector spaces over arbitrary infinite fields. Recently, Chad, Knight & Suabedissen [1] proved that the Continuum Hypothesis implies that there is a 2-point set included in the union of countably many concentric circles. Their conclusion is even stronger, being precisely the statement of the Theorem below.…”
mentioning
confidence: 99%
See 1 more Smart Citation